Tác động của chia sẻ thông tin đến hiệu suất chuỗi cung ứng vận tải hàng hoá xuất nhập khẩu: Nghiên cứu thực nghiệm tại khu vực Đông Nam Bộ Việt Nam - Nguyễn Thanh, Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The issue of information sharing has received a lot of attention in the supply chain but quantitative studies regards to this issue have not been much explored. This paper investigates the impact of information sharing on visibility, collaboration, and flexibility of the transportation supply chain, and examines how information sharing, visibility, collaboration, and flexibility directly and indirectly affect supply chain performance. This research used PLS-SEM model with 220 enterprises that are stakesholders in the import and export cargo transport supply chain in the Southeast region. Quantitative results show that information sharing positively and significantly influences supply chain visibility, collaboration, flexibility, and performance. Supply chain visibility positively impacts collaboration, flexibility, and performance while collaboration and flexibility significantly impact supply chain performance. Accordingly, the study argues that information sharing is the key to increasing the efficiency and competitiveness of the import and export cargo transport supply chain, especially in the context of the transport market's crisis after the COVID-19 as it is today